LEXICAL TRANSFORMATIONS IN ENGLISH–UZBEK TRANSLATION: SEMANTIC, FUNCTIONAL AND LINGUOCULTURAL ANALYSIS (SCIENCE TIME JOURNAL, 2026)
This article investigates lexical transformations in English–Uzbek translation from semantic, functional, and linguocultural perspectives. Translation is viewed not as a mechanical replacement of lexical items, but as a complex interpretive process involving semantic equivalence, contextual adaptation, stylistic appropriateness, and cultural transfer. The study focuses on the classification of lexical units, the problem of equivalent and non-equivalent vocabulary, and the main types of lexical transformations used in translation practice. Special attention is paid to concretization, generalization, omission, antonymic translation, and compensation as mechanisms that help preserve meaning and communicative effect in the target text. The article argues that lexical transformations are indispensable in English–Uzbek translation because of structural, semantic, and cultural differences between the two languages. The scientific significance of the research lies in its attempt to systematize lexical transformations not only as technical operations but also as functionally and culturally motivated strategies. The practical value of the article is determined by its relevance for translator training, literary translation, and translation-oriented language instruction.